Whipple’s disease – a rare and challenging complication in a patient with Crohn’s disease - Bulut, Kerem; Markova, Antoaneta; Canbay, Ali E.; Schmidt, Wolfgang E.; Kahraman, Alisan (Zeitschrift für Gastroenterologie, 2022)
Introduction Whipple’s disease (WD) is a rare and infectious condition leading to multi-organ impairment caused by Tropheryma whipplei (TW), a ubiquitously occurring bacterium. TW can be detected in tissues by histological detection of PAS (“periodic acid-ship reaction”)-positive macrophages and by polymerase-chain-reaction (PCR). Clinically, WD is often characterized by diarrhea, abdominal pain, and weight loss. These symptoms are also typical for a flare in Crohn’s disease (CD) and, therefore, can lead to fatal misdiagnosis and wrong treatment by using biologics (e.g., anti-TNF-α).Case report We here report a young male patient with pre-existing CD. The patient’s symptoms were misinterpreted as a flare of CD and illustrate the multifaceted nature of WD. After intensifying immunosuppressive therapy, the patient developed therapy-refractory diarrhea with several opportunistic infections with a final, fatal outcome.Conclusion Patients with inflammatory bowel disease (IBD) are not only at risk from infectious complications known with clostridium difficile or cytomegalovirus (CMV); infection with WD should also be ruled out by endoscopy and biopsy before the escalation of the immunosuppressive regime.
Keywords: Morbus Crohn; Morbus Whipple